РОЛЬ ДЕКОРАТИВНО-ПРИКЛАДНОГО ИСКУССТВА КАРАКАЛПАКСКОГО НАРОДА В РАЗВИТИИ ХУДОЖЕСТВЕННО-ТВОРЧЕСКИХ СПОСОБНОСТЕЙ СТУДЕНТОВ - Уразимова, Т.В. (SCIENCE and SOCIETY, 2020)
The article is devoted to the modern content and the role of the educational process and importance of decorative-applied arts of the karakalpak folk. Since attention increased in modern society to problem of the unceasing artistic education.Not the last role is played here by aesthetic education, contributing to enhance the development of philosophy, intellectual and creative potential of the individual. Therefore, the process of education should be based on creating conditions for education of creative personality, ready for a dialogue, collaboration and co-creation in various spheres of life.